2011
DOI: 10.1002/mds.23954
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind, placebo‐controlled trial of safinamide as add‐on therapy in early Parkinson's disease patients

Abstract: Safinamide is an α-aminoamide with both dopaminergic and nondopaminergic mechanisms of action evaluated as an add-on to dopamine agonist (DA) therapy in early-stage PD. In this 24-week, double-blind study, patients with early PD receiving a stable dose of a single DA were randomized to once-daily safinamide 100 mg, safinamide 200 mg, or placebo. The primary efficacy variable was UPDRS part III (motor examination) total score. Analysis was hierarchical: 200 mg of safinamide versus placebo was tested first; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 20 publications
4
94
1
Order By: Relevance
“…Two phase III clinical trials have been conducted in early PD with patients receiving dopamine agonists and two in midto late-stage PD for patients receiving levodopa with motor fluctuations [71][72][73][74]. In a 24-week randomized placebocontrolled trial of patients with early PD, the 100 mg/day dose of safinamide was associated with significant improvement in UPDRS part III and part II (ADL scale), and the Clinical Global Impression scale compared with placebo, while the 200 mg/day was not [71]. The MOTION trial evaluated safinamide 50 and 100 mg/day as an add-on to a dopamine agonist in early PD and demonstrated improvement in UPDRS III and quality of life in the PD questionnaire (PDQ-39) measures compared with placebo for the 100-mg dose [72].…”
Section: Safinamidementioning
confidence: 99%
See 1 more Smart Citation
“…Two phase III clinical trials have been conducted in early PD with patients receiving dopamine agonists and two in midto late-stage PD for patients receiving levodopa with motor fluctuations [71][72][73][74]. In a 24-week randomized placebocontrolled trial of patients with early PD, the 100 mg/day dose of safinamide was associated with significant improvement in UPDRS part III and part II (ADL scale), and the Clinical Global Impression scale compared with placebo, while the 200 mg/day was not [71]. The MOTION trial evaluated safinamide 50 and 100 mg/day as an add-on to a dopamine agonist in early PD and demonstrated improvement in UPDRS III and quality of life in the PD questionnaire (PDQ-39) measures compared with placebo for the 100-mg dose [72].…”
Section: Safinamidementioning
confidence: 99%
“…Recently, rasagiline was shown to be an effective adjunct to dopamine agonists (ropinirole and pramipexole) in improving motor symptoms [82]. Likewise, evidence is now growing that safinamide can be effectively added to both dopamine agonists and levodopa in mid-to late-stage PD [71,73,74,77,83]. MAO-B inhibitors can be successfully combined with almost any class of antiparkinson medications due to their low risk for drug-drug interactions, and, as adjunct therapy, they constitute a valuable addition to a clinician's drug armamentarium.…”
Section: Combination Therapiesmentioning
confidence: 99%
“…An inhibitor of MAO-B and of glutamate release, safinamide pre-treatment of MPTPlesioned dyskinetic macaque monkeys has been found to prolong response to levodopa and reduce levodopa-induced dyskinesias (LIDs) in a dose-dependent manner [32]. These effects have been largely reproduced in clinical trials of safinamide in PD [33,34].…”
Section: -Hydroxydopamine-lesioned Modelmentioning
confidence: 99%
“…Recently, blocking voltage depended sodium channels) by preventing dyskinesia and motor fluctuations in early PD patients [37]. Further randomized and double blind phase II/III studies demonstrated the anti-parkinson efficacy of safinamide therapy in PD patients [38]. Dopamine (post-synaptic D2 receptors) agonists such as non-ergot derivatives (pramipexole, ropinirole and rotigotine) are also used in early PD patients (above age of 60 years).…”
Section: Pharmacotherapy and Management Of Parkinson's Diseasementioning
confidence: 99%